EVALUASI PENERAPAN KURIKULUM 2013 PADA MATA PELAJARAN AQIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 1 KOLAKA KABUPATEN KOLAKA - Hamsidar Hamsidar (Jurnal Teknologi Pendidikan Madrasah, 2020)
The problem in this study is that researchers only reveal the evaluation of the implementation of the 2013 Curriculum in Aqidah Akhlak Subjects at Madrasah Tsanawiyah Negeri 1 Kolaka, Kolaka Regency which includes: planning evaluation, evaluation of the learning implementation process, evaluation of the assessment of Aqidah Akhlak subjects and the obstacles and solutions that are carried out. to overcome these obstacles.This research is a qualitative research. This evaluation method focuses on evaluating teacher understanding, planning evaluation, evaluating the implementation process, evaluating assessment and assessment results as well as obstacles and solutions in the implementation of the 2013 Curriculum. Data obtained from interviews, observations, and documentation and questionnaires. Data analysis used, namely, data reduction, data analysis and presentation of conclusions. The data validity test used observation persistence, tringulation, descriptive analysis.The results of this study indicate that the evaluation of the implementation of the 2013 curriculum in the subject of Aqidah Akhlak in MTs. Negeri 1 Kolaka. The results of the evaluation at the teacher planning stage make planning according to the guidelines. Evaluation of the teacher implementation process properly according to what was planned. Evaluation of the learning implementation process goes well which affects the absorption of students well, so that learning outcomes can be achieved properly (complete). The obstacles encountered were the teachers were not able to carry out all forms of assessment and the lack of learning facilities and infrastructure. Therefore, the solution that must be taken to overcome this is to strengthen knowledge for educators through workshops, training, and the use of the Subject Teacher Deliberation Forum. (MGMP) and make the most of the existing infrastructure in MTs. Negeri 1 Kolaka.